2006
DOI: 10.1097/01.ta.0000197177.13379.f4
|View full text |Cite
|
Sign up to set email alerts
|

Do Trauma Patients with a Glasgow Coma Scale Score of 3 and Bilateral Fixed and Dilated Pupils Have Any Chance of Survival?

Abstract: Patients with GCS of 3 and BFDP have a dismal prognosis. These patients have suffered devastating brain injuries and tend to be hemodynamically unstable. Clinicians, however, are less likely to aggressively treat BFDP patients than RP patients. Further prospective studies are required to determine which patients with GCS of 3 and BFDP are likely to benefit from aggressive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 27 publications
2
63
2
2
Order By: Relevance
“…8 Tien et al reported an overall mortality rate of 76.8% in 173 patients with GCS score of 3; the mortality was 100% in patients with fixed, dilated pupils and 42% in patients with reactive pupils. 50 Other studies in adults show relatively consistent factors that correlate with survival and, conversely, death. Factors that are associated with poor survival include hypoxia, extremes of age, hypotension, hypercarbia, hyperglycemia, mechanism of injury, and hypothermia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Tien et al reported an overall mortality rate of 76.8% in 173 patients with GCS score of 3; the mortality was 100% in patients with fixed, dilated pupils and 42% in patients with reactive pupils. 50 Other studies in adults show relatively consistent factors that correlate with survival and, conversely, death. Factors that are associated with poor survival include hypoxia, extremes of age, hypotension, hypercarbia, hyperglycemia, mechanism of injury, and hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other published studies. 8,26,50 In patients with an absent pupil- lary response, the next most correlative predictive variable in our study was the presence of hypothermia. Note that we did not therapeutically induce hypothermia in any patient.…”
Section: Predictive Variables For Clinical Outcomementioning
confidence: 95%
See 1 more Smart Citation
“…In comparison, 42.0% of the patients with reactive pupils died. 26 Whether the death of patients in the intensive care unit with severe TBI significantly contributes to shorter LOS and lower hospital treatment cost should be elucidated with future study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that patients with a GCS of 3 as well as fixed and dilated pupils have no reasonable chance of recovery. Similarly, in a retrospective study of Tien et al, [32] they found that patients with an initial GCS of 3 and bilateral fixed and dilated pupils had a 100% in-hospital mortality rate. Despite the hopeless results of these reports, Chamoun et al [33] presented a survival rate of 21.3% and a good outcome rate of 1.5% in this patient group in a recent study.…”
Section: Gcs Score Icp and Cpp Changes And Prognosismentioning
confidence: 99%